Hubungan Terpaan Film “A Man Called Ahok” Dengan Citra Basuki Tjahaja Purnama (Ahok) Dalam Masyarakat - Kartika, Hernanda; Amanda Gelgel, Ni Made Ras; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2022)
ABSTRACT "A Man Called Ahok" is a national biopic film that i n its release, this film raises opinions of many people related to its emergence of the political contestation season and of Ahok’s controversial figure. Ahok is assumed to have a mission to win the sympathy of the people, with a narrative of Ahok's life values ??during Bangka Belitung. The purpose of this study is to explain the relationship between exposure of the film "A Man Called Ahok" with the image of Basuki Tjahaja Purnama (Ahok) in society. Th e study uses explanation quantitative research methods with the theory of media exposure, image, and media dependencies. The results indicate that there is a relationship between the exposure of the film "A Man Called Ahok" with the image of Basuki Tjahaja Purnama (Ahok) in the communit y.   Keywords : Biopic, Film Exposure, Image, Media Dependency